EFFICIENCY OF THE DEVELOPMENT AND ORGANIZATIONAL AND ECONOMIC STIMULATION OF BUSINESS ACTIVITIES IN AGRICULTURE - Opayev Biysenbay Aymanovich (American Journals, 2024)
Today, the author gives feedback on the effectiveness of the development of business activities in agriculture and the organizational and economic incentives in our country and has developed scientific proposals and recommendations.
Keywords: Economy, family business, organizational and economic foundations, mechanisms.